2008
DOI: 10.1002/ejoc.200800043
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Gold(I)‐Catalyzed Ring Expansion of Cyclopropanols: Theoretical Calculations Uncover a Bottle‐Neck 1,4‐H Shift and Suggest Adequate Reaction Conditions

Abstract: The mechanism of the one‐carbon ring‐expansion reactions of 1‐(1‐propynyl)cyclopropanol (1; R = Me), (1R*,2R*)‐1‐ethynyl‐2‐isopropylcyclopropanol (3), and (1R*,2S*)‐1‐(phenylethynyl)‐2‐isopropylcyclopropanol (4) catalyzed by [AuP(Ph)3]+ to yield the corresponding 2‐alkylidenecyclobutanones was theoretically investigated by B3LYP‐PCM calculations by using the LANL2DZ relativistic effective core potential for Au and the 6‐31G(d) basis set for the remaining atoms. The most favorable route for these rearrangements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 49 publications
5
17
0
Order By: Relevance
“…The promising results push us to try the reaction utilizing various Mn catalysts such as Mn 2 (CO) 10 , Mn(OAc) 2 , MnF 3 , MnCl 2 , and MnCO 3 (entries 3-7), unfortunately, no better result was obtained. Next, we investigated the reaction in other solvent, such as t BuOH, MeOH, DMF, 1,4-dioxane, DCE, CH 2 Cl 2 , THF, cyclohexane, and toluene (entries [8][9][10][11][12][13][14][15][16]. Solvent screening showed that protic polar solvent t BuOH and MeOH were also suitable for this reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The promising results push us to try the reaction utilizing various Mn catalysts such as Mn 2 (CO) 10 , Mn(OAc) 2 , MnF 3 , MnCl 2 , and MnCO 3 (entries 3-7), unfortunately, no better result was obtained. Next, we investigated the reaction in other solvent, such as t BuOH, MeOH, DMF, 1,4-dioxane, DCE, CH 2 Cl 2 , THF, cyclohexane, and toluene (entries [8][9][10][11][12][13][14][15][16]. Solvent screening showed that protic polar solvent t BuOH and MeOH were also suitable for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Transition-metal-catalyzed cyclopropanol chemistry to construct CÀ C and CÀ X (X = heteroatom) bond has been expanded significantly. [5,[6][7][8][9][10][11][12] Preliminary works mainly cover some precious metals, such as Ru, [6] Pd, [7] Ag, [8] and Au, [9] while recently more involve some inexpensive metals, such as Zn, [10] Cu, [11] Fe, [8d] and Mn. [12] Additionally, earth-abundant Mn complex, Mn(acac) 3 is an inexpensive Lewis acid, which has been widely used in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of counter ion [11,12] and solvent considered [13][14][15] plays a key role in driving the reaction process. Understanding the mechanism of such reactions is highly challenging and computational studies have always enlightened the chemists to unravel the mechanistic insights for such reactions [9,[16][17][18][19][20]. Reports have shown the importance of non-covalent interactions in directing the reaction path and thereby exemplifying the product formation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The counterion OTfH attacks the 'O' proceeding to the carboxylic acid adduct, 1-c via TS3-O-c2 and In7-O-c2.The formation of pyrone can also proceed through 1,3-oxygen shift (Scheme 1). Previous reports on the ring expansion of cyclopropanols suggest a single step for the ring formation[17]. Initially the corresponding transition state which involves the simultaneous breakage of O-C 1 bond and the formation of O-C 2 bond was looked at, which led to futile attempts.…”
mentioning
confidence: 99%
“…Notably, the experimental results showed that there must be a hydroxyl group on the cyclopropane ring to make the Toste's and Trost's reactions possible. [10][11][12][13] Therefore, the hydroxyl group on the cyclopropane ring was called the activated group for the ring expansion reaction of the synthesis for cyclobutane derivatives.…”
Section: Introductionmentioning
confidence: 99%